Assessment of capacity for cardiovascular disease control and prevention in Thailand: A qualitative study - Wichai Aekplakorn (2018)
The present study explored community members' knowledge and perceptions about cardiovascular disease (CVD), risk factors and prevention, and identified the current capacity of primary care providers to manage and control CVD at the provincial level. A qualitative study, including in-depth interviews and focus group discussions, was conducted in Suphan Buri Province, Thailand. Participants included community members, CVD patients and healthcare providers in health centers and hospitals. The results showed that community members had little knowledge about the symptoms and signs of heart attack or stroke. They perceived that existing health centers and community hospitals were not sufficiently equipped to treat CVD patients. Primary healthcare workers reported that they lacked skills to manage heart disease, particularly emergency care. Physicians said that they had too little time to educate patients and felt that medical schools should update their curricula, including practical training on CVD management in a low-resource setting. Nurses reported that they had inadequate training in health education for the prevention of CVD. There was a problem of inadequate feedback mechanisms in the existing referral system for continuing improvement. All of the health professionals agreed that more community participation and the involvement of non-health sectors and non-government organizations were needed in the national CVD control program. In conclusion, capacity building for strengthening CVD prevention and control at the primary care level should be implemented. The existing training and education systems have to be revised with an orientation towards health promotion and disease prevention. Publicity of CVD burden and preventive measures, and local programs, should be implemented with community participation.